The Effect of E-Service Quality on E-Loyalty with E-Satisfaction as a Mediation Among GoFood Users in the City of Padang - Fadilatussakinah, Fadilatussakinah; Whyosi Septrizola (Dinasti Review, 2025)
This study aims to analyze the effect of e-service quality on e-loyalty with e-satisfaction as a mediating variable among GoFood users in Padang City. This study uses a quantitative approach with a sample of 140 respondents selected through purposive sampling. Data were collected through an online questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that e-service quality has a positive and significant influence on e-loyalty, e-service quality has a positive and significant influence on e-satisfaction, and e-satisfaction has a positive and significant influence on e-loyalty. Additionally, e-satisfaction acts as a mediator in the relationship between e-service quality and e-loyalty. These findings conclude that improving e-service quality can enhance user satisfaction, which in turn strengthens customer loyalty toward the GoFood platform. This study contributes to understanding how digital service quality and customer satisfaction influence loyalty in the online food delivery industry.